(untitled) (GESTIÓN Y TENDENCIAS, 2018)
This article describes the Selective Stock Price Index (IPSA), its composition, and its relevance as the main return index of the Chilean stock market. It then analyzes the main factors that influenced its performance in the 2015-2017 period, with particular attention to the rally observed in 2016 and the volatility observed during the presidential election period. It concludes by presenting some outlooks for its performance in 2018.